2015
DOI: 10.22495/cocv12i3c5p8
|View full text |Cite
|
Sign up to set email alerts
|

Gender diversity in large listed Indian companies

Abstract: This paper aims to examine the effectiveness of gender diverse boards on financial performance in large listed Indian companies by taking a resource dependency perspective. Gender diverse board is measured by presence of the independent female director on the board. Further, financial performance is measured by the market performance measure taking Tobin’s Q. This relationship is examined by collecting information for eleven financial years from 2003 -13. Panel regression model is employed to assess the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Both studies found that gender diversity and firm performance are positively associated. The findings of Haldar et al, (2015) in India confirmed this positive relationship and support the findings in Malaysia. In Nigeria, studies by Oba and Fodio (2013), Garba and Abubakar (2014) and Oyewale et al (2016) produced similar trend.…”
Section: Literature Reviewsupporting
confidence: 84%
See 1 more Smart Citation
“…Both studies found that gender diversity and firm performance are positively associated. The findings of Haldar et al, (2015) in India confirmed this positive relationship and support the findings in Malaysia. In Nigeria, studies by Oba and Fodio (2013), Garba and Abubakar (2014) and Oyewale et al (2016) produced similar trend.…”
Section: Literature Reviewsupporting
confidence: 84%
“…Similar to studies from developed markets, findings from emerging markets offer mixed results though a large number of empirical works show positivity between gender diversity and performance. While a number of studies from emerging markets (Julizaerma & Sori, 2012;Oba & Fodio, 2013;Shehata, 2013;Garba & Abubakar, 2014;Haldar, Shah & Rao, 2015;Jonty & Mokoteli, 2015;Tu, Loi & Yen, 2015;Oyewale, Oloko & Olweny, 2016;Hassan & Marimuthu, 2018; Lee-Kuen, Sok-Gee & Zainudin, 2017) report positive relationship, others (Yasser, 2012;Dabor, Isiavwe, Ajagbe & Oke, 2015: Kilic, 2015Abu, Okpeh, & Okpe, 2016;Solakoglu & Demir, 2016;Hassan & Marimuthu, 2018) indicate either none or negative association between the two variables. Several studies done in Malaysia on the relationship between gender diversity and performance have also reported positive results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial Performance is the major element that incentivises the investors to make investments into a firm in the expectations of gaining good returns, and it is on this basis that the performance of the board of directors is also evaluated. We measured financial performance by using a market based measure rather than the accounting based measure, since the accounting based measures are based on the past results and might not reflect the changes in the governance norms immediately (Haldar et al, 2015).…”
Section: Dependent Variablementioning
confidence: 99%
“…Secondly, it reflects the market's expectations of future earnings and is, thus, a good proxy for a firm's competitive advantage (Montgomery & Wernerfelt, 1988). Hence, Tobin's Q was used as a proxy for measuring the performance, based on the work of Ahern and Dittmar (2012), Haldar et al (2015), and Campbell et al (2008) for various years. Tobin's Q is calculated using the Chung and Pruitt (1994) formula, which is, market valuation of shares plus debt divided by the total assets.…”
Section: Tobin's Qmentioning
confidence: 99%
See 1 more Smart Citation